2002
DOI: 10.1557/proc-758-ll5.7
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design, Freeform Fabrication and Testing of Nylon-6 Tissue Engineering Scaffolds

Abstract: Advanced and novel fabrication methods are needed to build complex three-dimensional scaffolds that incorporate multiple functionally graded biomaterials with a porous internal architecture that will enable the simultaneous growth of multiple tissues, tissue interfaces and blood vessels. The aim of this research is to develop, demonstrate and characterize techniques for fabricating such scaffolds by combining solid freeform fabrication and computational design methods. When fully developed, such techniques are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Rapid prototyping (RP) [174,175] or solid free-form (SFF) [115,176,177] fabrication, are common terms for a group of techniques that model a scaffold directly from a computer-aided design (CAD) data set. RP techniques mostly build up a specific body shape by the selective addition of material, layer-by-layer, guided by a computer program [178].…”
Section: Rapid Prototyping/solid Free-form Fabricationmentioning
confidence: 99%
“…Rapid prototyping (RP) [174,175] or solid free-form (SFF) [115,176,177] fabrication, are common terms for a group of techniques that model a scaffold directly from a computer-aided design (CAD) data set. RP techniques mostly build up a specific body shape by the selective addition of material, layer-by-layer, guided by a computer program [178].…”
Section: Rapid Prototyping/solid Free-form Fabricationmentioning
confidence: 99%
“…Tan et al [10] and Chua 2 METHODS et al [11] demonstrated the ability of SLS to fabricate physically blended hydroxyapatite (HA)-poly(ether-2.1 Polyamide, hydroxyapatite raw materials and ether-ketone) (PEEK) and HA-poly(vinyl alcohol) hydroxyapatite-polyamide composite composites for tissue scaffold development and powders observed micropores on the scaffold surface. Das and co-workers [12][13][14] investigated the production For this research, commercial SLS material-grade fine nylon was used as the binder, to isolate and of HA-poly-(l-lactic acid) (PLLA) parts by SLS and found that the ultimate compressive strength and clarify variables within the investigation and to evaluate the viability of using the SLS process to fabelastic modulus were in the lower limits of reported values for cancellous bone. In addition, using comricate structures with the maximum HA content possible and to assess the internal structure fabriputational designs, this technique was used to manufacture tissue-engineering scaffolds with periodic cated.…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al 23 and Chua et al 24 demonstrated the ability of SLS to fabricate physically blended hydroxyapatite (HA)-poly (ether-ether-ketone) (PEEK) and HA-poly (vinyl alcohol) composites for tissue scaffold development and observed micropores on the scaffold surface. Das et al 25 investigated the production of HA-poly-(l-lactic acid) (PLLA) parts by SLS and noted the ultimate compressive strength and elastic modulus to be in the lower limits of reported values for cancellous bone. During the early stages, application of laser sintering to fabricate implants with composites of HA and b-TCP materials 26 involved coating, reinforcing, and blending of the ceramic powder with a secondary polymeric binder.…”
Section: Introductionmentioning
confidence: 99%